Una apreciación a la promoción de la educación universitaria y el crecimiento de su oferta en la ciudad de Lima para el periodo 1990-2010 - Ospino Edery, Juan José (2011)
This study, develops a particular appreciation on the implications of the offer of university education in the city of Lima on the part of the private universities that are formed and suited as a result of the implementation of the D. L. 882 also known as law for the promotion of university education or law of the university company given in the year 1996, as well as his side effect in the main state universities. The topics of analysis that are considered to enable the answer to the problem of What has been carrying out the development of university education provision in the city of Lima as a result of the current policy of promoting the private education?, are: A university law review from 1970 to 2010; findings of the mission of higher education in Peru; neoliberalism and education; evolution of the Supply of University Education in the city of Lima for the period 1980-2010; balance between supply / demand and vacancies / applicants of college education in the city of Lima private universities, and evolution of the pressure index (candidates / vacancies); Offered professional, private universities in the city of Lima.